2011
DOI: 10.1118/1.3664003
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Modification of the standard gain correction algorithm to compensate for the number of used reference flat frames in detector performance studies

Abstract: The authors show that the method presented in the study (a) leads to the maximum DQE value that one would have by using the conventional method and very large number of frames and (b) has been compared to an independent gain correction method based on the subtraction of flat-field images, leading to identical DQE values. They believe this provides robust validation of the proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…62 During the NPS measurements described in this paper, the FPN was removed using a gain and offset correction algorithm without introducing propagated uncorrelated noise to the corrected flat images. 68 The total electronic noise can be given by…”
Section: Appendix B: Electronic Noise Of 3-t Apsmentioning
confidence: 99%
“…62 During the NPS measurements described in this paper, the FPN was removed using a gain and offset correction algorithm without introducing propagated uncorrelated noise to the corrected flat images. 68 The total electronic noise can be given by…”
Section: Appendix B: Electronic Noise Of 3-t Apsmentioning
confidence: 99%
“…The signal-to-noise ratio (SNR) for the flood-field images is denoted by SNR s . It is noted that the gain-offset correction of flood-field images is a standard procedure in digital imaging to avoid contamination in flood-field images from nonstochastic processes, and it is based on normalization with an average reference flood field (or flat field) [25][26][27]. The offset correction accounts for the nonuniform dark current effects in pixels, while the gain correction accounts for the nonuniform response of pixels.…”
Section: Large-area Signal and Noise Analysismentioning
confidence: 99%
“…A previous study used the integral of the NPS which is equivalent to the rms noise (i.e., standard deviation). 37,41 In the literature, the power-law model has been extensively used to characterize the noise in many natural backgrounds. 38 Additionally, a number of authors have found that the power spectrum of the anatomical noise in projection mammography had the power-law form.…”
Section: Metricmentioning
confidence: 99%